Computational analysis of thermal and structural failure criteria of a multi-storey steel frame exposed to fire. (1st February 2019) - Rackauskaite, Egle; Kotsovinos, Panagiotis; Jeffers, Ann; Rein, Guillermo
Highlights: Critical temperature as a failure criterion for structures exposed to fire is studied. It is compared to structural stability, utilization, and beam deflection criteria. A 2D generic 10-storey steel framed building is modelled using LS-DYNA. In total, 117 different scenarios are investigated. We show that the critical temperature is a conservative failure criterion. Abstract: Structural fire design, until recently, has only assumed uniform fires inside the compartment, and the assessment of structural failure has been often based on a critical temperature criterion. While this criterion, to some extent, may be able to indicate the temperature at which the structural element is near to failure, it is based on standard fire tests and, therefore, its validity is limited to individual members exposed to uniform temperatures. It is unclear how representative a critical temperature criterion is of structural failure in the case of multi-story structures, particularly in the case of non-uniform fires such as travelling fires. Therefore, the aim of this study is to assess the validity of the critical temperature criterion for structures exposed to non-uniform fires and compare it to uniform fires. A generic 10-storey steel framed building is modelled using the finite element software LS-DYNA. In total, 117 different scenarios are investigated to cover a wide range of conditions of interest for design of modern steel buildings, varying the fire exposure (travelling fires, Eurocode parametric fires, ISO-834 standard fire, and SFPE standard), floor where the fire is burning, beam section size, and applied fire protection to the beams. For the different fire exposures considered, the analysis predicts structural failure at different times, in different locations and floors, and different failure mechanisms. Moreover, it is shown that there is no single worst case fire scenario: different fires can lead to failure in different structural ways. The comparison of the various structural and thermal failure criteria (ultimate strain, utilization, mid-span deflection, and critical temperature) show that there is no consistency between them, revealing a far more complex problem than reported in the literature. Lastly, this work has illustrated that the critical temperature criterion does not predict accurately the structural failure in time, space or failure mode of steel structures subjected to both uniform and non-uniform fires. Structural failure can only be predicted by advanced structural analysis, and, therefore, heat transfer analysis alone is not sufficient for design. Nevertheless, it was shown that the use of the critical temperature leads to conservative results for simple steel structures. For the sake of comprehensive design, a range of different fire scenarios, including both uniform and non-uniform, should be part of the analysis such that all likely structural responses and failure modes can be considered.